Impact of host physiology and external stressors on the bacterial community of Schmidtea mediterranea - Karolien Bijnens; Sofie Thijs; Rossella Alfano; Breanne McAmmond; Jonathan Van Hamme; Tom Artois; Michelle Plusquin; Jaco Vangronsveld; Karen Smeets (Scientific Reports)
Abstract To fully comprehend host-microorganism interactions, it is crucial to understand the composition and diversity of the microbiome, as well as the factors that shape these characteristics. We investigated microbiome variation using the freshwater planarian Schmidtea mediterranea, an invertebrate model in regeneration biology and (eco-)toxicology, by exposing the organisms to various controlled conditions. The microbiome composition exhibited high variability, with most of the bacteria belonging to the Betaproteobacteria. Among the diverse microbial communities, a few genera, such as Curvibacter, were consistently present, but exhibited significant alterations in response to changing conditions. The relative abundance of Curvibacter fluctuated during the regeneration process, initially increasing before returning to a composition similar to the beginning situation. After applying external stress, the relative abundance of Curvibacter and other genera decreased. Variation over time, between different origin laboratories and between individuals, showed that additional, yet to-be-identified, factors of variation are present. Taking all results together, our study provides a solid basis for future research focusing on bacterial functionality in planarians and other invertebrates.